The role of the Federal Chancellor in the German political system - نحيلي, سعيد; صالح , علي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Germany is considered to be one of the most influential countries in the Political and economic spheres, not only in Europe, but also around the globe. Arabic texts and literature in Law do not include sufficient researches about this country, which is rich in historical and political events. Therefore, I chose this research to highlight one of the foundations of Germany's political system, the Federal Chancellor. The German political system is one of the stable parliamentary systems, in which the Federal Chancellor is a key player and considered the engine of democratic dynamism. In the first section of this research, we will talk about the chancellor position in the federal government, showing the importance of the federal government in the German political system and the role played by the federal chancellor. In the second section of this paper, we will talk about the relationship between the Federal Chancellor and the main legislative authority, which is the Federal Parliament (Bundestag).